Exploring the needs and challenges of parents and their children in childhood epilepsy care: A qualitative study - Wo, Su Woan; Ong, Lai Choo; Low, Wah Yun; Lai, Pauline Siew Mei (Elsevier, 2018)
Because of the nature of epilepsy, and the unpredictability of seizure recurrence, epilepsy requires long-term treatment with medications. As a consequence, epilepsy has a negative pervasive impact in children with epilepsy (CWE), and their parents. Hence, our aim was to explore the needs and challenges of parents and their CWE. In-depth interviews (IDIs) were conducted with 15 families (12 mothers and 3 fathers) and 15 CWE (aged 8–18 years). Data were transcribed verbatim and thematically analyzed using the descriptive phenomenology approach. The experiences of parents and their CWE could be divided into two time frames: “experiences during a child's first seizure” and “experiences whilst growing up with epilepsy”. Parents’ main concerns and worries were regarding their child's physical health, psychological and emotional wellbeing, academic achievement, and future. The children's main concerns were restrictions imposed, their interpersonal relationship with peers, and being independent in the future. Parents reported that they needed epilepsy-related information, continuity of care, and a parental support group, while CWE reported that their main needs were independence and autonomy. The views of parents and their child with epilepsy were similar in physical functioning and academic achievement. However, parents and children had different views on how epilepsy impacted on the child emotionally, as well as behavioral and interpersonal relationship with peers.